JAMINAN SOSIAL SEBAGAI HAK KONSTITUSIONAL: KETIDAKSETARAAN PERLINDUNGAN PEKERJA INFORMAL DI INDONESIA - Angelia, Rina Rahma Ornella; Fitria, Yenni; Desmon, Andi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Social security is a constitutional right inherent in every citizen and is guaranteed by the 1945 Constitution of the Republic of Indonesia. As a state based on law that adheres to the principles of a welfare state, Indonesia has a constitutional obligation to provide a fair, inclusive, and non-discriminatory social security system for all workers. However, in its implementation, disparities in social security protection between formal and informal workers persist. This article aims to analyze the position of social security as a constitutional right within Indonesia’s national legal system and to identify the legal and policy measures undertaken by the government to address such disparities. This study employs a normative juridical research method using statutory and conceptual approaches through an examination of primary, secondary, and tertiary legal materials. The findings indicate that inequality in social security protection for informal workers is influenced by several factors, including unstable income conditions, limited regulations specifically governing the legal status of informal workers, low levels of social security literacy, as well as administrative and bureaucratic barriers in the participation process. Therefore, strengthening explicit regulatory frameworks, adjusting contribution payment schemes to be more flexible, and enhancing public outreach alongside simplifying administrative procedures are necessary to achieve equitable social security protection in accordance with constitutional mandates. Keyword: Social security, constitutional rights, informal workers, BPJS Employment, social justice